MENINGKATKAN KEMAMPUAN BAHASA MELALUI KEGIATAN BERMAIN PERAN KELOMPOK B - Purwanti, Yayuk (Jurnal Analisis Pendidikan Sosial, 2024)
In the national education system law,it is ststed that early childhood education is a coaching effort aimed at children from birth to the age of six which is carried out through the provision of educational stimuli to assit physical and spiritual growth and development so that children have readiness to enter education. Furthermore, early childhood education aims to help student develop various potensials, both physical and physycological, which include religious and moral values, social emotional, Independence, cognitive, language, motor and art. This research is the result of observations from GPO videos and the low ability of children’s language understanding in INSAN CENDEKIA MANDIRI kindergarten, Tulangan Sidoarjo, due to the lack of media and interesting games for student.this study aims to develop children’s language skills through role playing activities. This research is a classroom action reseach which consist of 2 cycles which includes the stages of planning, implementation, observation and reflection. The subjects of this study were group B students for the 2019-2020 academic year. The results of this study indicate an increase in the ability of children in language skills.the percentage of children’s abilities in the first cycle was 60%,the second cycle increased to 90%. Through role playing activities can improve children’s language development.